PEMBELAJARAN MENDALAM MELALUI MEDIA BUKU DIARY DALAM MENGEMBANGKAN KETERAMPILAN MENULIS DAN BERBICARA SISWA - Estuning Dewi Hapsari; Dedy Richi Rizaldy; Eni Winarsih (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The purpose of this study is to describe the application of in-depth learning using diary media to develop writing and speaking skills in third-grade students. The research approach used is qualitative with a descriptive qualitative research type. The research data is in the form of descriptions of learning during the learning activities. The research subjects are third-grade students. Data collection techniques used are observation, interviews, documentation, and field notes. Data analysis consists of data reduction, presentation, and conclusion. The results of the study indicate that in-depth learning with the help of diary media is able to develop students' writing and speaking skills.